1970
DOI: 10.1136/bmj.1.5691.267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Endocrine Side-effects of Methylprednisolone Acetate as used in Hay-fever

Abstract: Summary: Eight patients were treated with two 80-mg.doses of methylprednisolone acetate (Depo-Medrone), given at an interval of two weeks. Pituitary-adrenal function was assessed before, during, and after treatment.Plasma cortisol levels were depressed maximally 72 hours after each injection of methylprednisolone acetate, and then gradually returned to normal. The adrenocortical response to administered corticotrophin was similarly affected; in seven patients normal values were again recorded three weeks after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…Furthermore, the individual lower leg growth curves indicated that the short-term growth suppressive effect of methylprednisolone acetate treatment was only transient. This is in accordance with previous reports of a transient suppressive effect of depot steroids on the adrenocortical secretion of cortisol in adults (4,5). Thus our data suggest that a single injection of methylprednisolone acetate may not be associated with any effect on long-term growth.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the individual lower leg growth curves indicated that the short-term growth suppressive effect of methylprednisolone acetate treatment was only transient. This is in accordance with previous reports of a transient suppressive effect of depot steroids on the adrenocortical secretion of cortisol in adults (4,5). Thus our data suggest that a single injection of methylprednisolone acetate may not be associated with any effect on long-term growth.…”
Section: Discussionsupporting
confidence: 94%
“…Topical and systemic glucocorticosteroids have been found to be superior to oral antihistamines in controlling the symptoms (1)(2)(3). Systemic glucocorticosteyoids are often given as a single injection of a long-acting depot steroid at the beginning of the pollen season (4)(5)(6). However, such treatment may be associated with a risk of serious side effects, such as suppression of longitudinal growth (2,6,7).…”
Section: Od Wolthers Siriusvej 9 Dk-8270 Hqjbjerg Denmarkmentioning
confidence: 99%
“…It showed that the effect of 80 mg methylprednisolone on nasal blockage was marked and lasted for more than 4 weeks. That this beneficial effect outlasted the pharmacological action ofthe drug, estimated by the effect on the hypothalamic-pituitary-adrenal axis to be about 2 weeks (8,9), suggests that an impact steroid therapy in rhinitis can break some viscious circles, probably caused by chronic inflammation and the development of mucosal hyperreactivity ("priming effect") (5).…”
Section: Discussionmentioning
confidence: 99%
“…Depot injections of the microcrystailine ester methylprednisolone-acetate (DepoMedrone®), equivalent to 100 mg of prednisolone, are used widely for the control of hay fever. Such injections probably suppress adrenal function for up to 3 weeks and in a few cases cause atrophy at the site of injection [59]. However, they are effective, particularly in the control of nasal obstruction [60].…”
Section: Corticosteroidsmentioning
confidence: 99%